Genetic differentiation of Rubus chamaemorus populations in the Czech Republic and Norway after the last glacial period. Issue 11 (2nd May 2018) - Leišová‐Svobodová, Leona; Phillips, Jade; Martinussen, Inger; Holubec, Vojtěch
Abstract: The population structure of cloudberry ( Rubus chamaemorus L.), collected from Krkonose Mountains (the Czech Republic), continental Norway and Spitsbergen, was examined using microsatellite analyses (SSR). Among 184 individuals, 162 different genotypes were identified. The overall unbiased gene diversity was high ( h ^ = 0.463 ). A high level of genetic differentiation among populations ( F ST = 0.45; p < .01) indicated restricted gene flow between populations. Using a Bayesian approach, six clusters were found which represented the genetic structure of the studied cloudberry populations. The value of correlation index between genetic and geographical distances ( r = .44) indicates that gene flow, even over a long distance, could exist. An exact test of population differentiation showed that Rubus chamaemorus populations from regions (Krkonose Mountains, continental Norway and Spitsbergen) are differentiated although some individuals within populations share common alleles even among regions. These results were confirmed by AMOVA, where the highest level of diversity was found within populations (70.8%). There was no difference between 87 pairs of populations (18.7%) mostly within cloudberry populations from continental Norway and from Spitsbergen. Based on obtained results, it is possible to conclude that Czech and Norwegian cloudberry populations are undergoing differentiation, which preserves unique allele compositions most likely from original populations during the last glaciation period. This knowledge will be important for the creation and continuation of in situ and ex situ conservation of cloudberry populations within these areas. Abstract : The population structure of cloudberry ( Rubus chamaemorus ), collected from Krkonose Mountains (the Czech Republic), Norway and Svalbard, was examined using a microsatellite analyses (SSR). Data analysis showed that Czech and Norwegian cloudberry populations are undergoing differentiation which preserves unique allele compositions most likely from original populations from the last glaciation period. This knowledge will be important for the creation and continuation of in situ and ex situ conservation of cloudberry populations within these areas.